2001
DOI: 10.1016/s0168-6496(01)00134-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of arbuscular mycorrhizal fungi colonising arable crops

Abstract: We used differences in small subunit ribosomal RNA genes to identify groups of arbuscular mycorrhizal fungi that are active in the colonisation of plant roots growing in arable fields around North Yorkshire, UK. Root samples were collected from four arable fields and four crop species, fungal sequences were amplified from individual plants by the polymerase chain reaction using primers NS31 and AM1. The products were cloned and 303 clones were classified by their restriction pattern with HinfI or RsaI; 72 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
175
6
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(209 citation statements)
references
References 22 publications
22
175
6
6
Order By: Relevance
“…The Glomeraceae has been shown to have the ability to colonize new roots via their mycelium or colonized root fragments (Tommerup and Abbott, 1981) and can do so at a higher sporulation rate and intensity than species from Acaulosporaceae and Gigasporaceae (Hart and Reader, 2002). Similar to present study, domination of the AMF communities by Glomus species has also been reported in forest (Husband et al, 2002a,b;Öpik et al, 2003), grassland (Vandenkoornhuyse et al, 2002a;Scheublin et al, 2004;Santos et al, 2006), wetland (Wirsel, 2004) and agricultural (Daniell et al, 2001;Hijri et al, 2006) soils.…”
Section: Amf Diversity In the Temperate Steppesupporting
confidence: 87%
See 2 more Smart Citations
“…The Glomeraceae has been shown to have the ability to colonize new roots via their mycelium or colonized root fragments (Tommerup and Abbott, 1981) and can do so at a higher sporulation rate and intensity than species from Acaulosporaceae and Gigasporaceae (Hart and Reader, 2002). Similar to present study, domination of the AMF communities by Glomus species has also been reported in forest (Husband et al, 2002a,b;Öpik et al, 2003), grassland (Vandenkoornhuyse et al, 2002a;Scheublin et al, 2004;Santos et al, 2006), wetland (Wirsel, 2004) and agricultural (Daniell et al, 2001;Hijri et al, 2006) soils.…”
Section: Amf Diversity In the Temperate Steppesupporting
confidence: 87%
“…This suggests either a site-dependent response to N, or functional diversity within this species. DL-Glo15, which can be assigned to F. mosseae can also be considered a generalist fungal species since it is very common in various ecosystems, including temperate arable fields (Daniell et al, 2001), tropical forests (Husband et al, 2002a,b), seminatural grasslands (Vandenkoornhuyse et al, 2002a) and wetlands (Wirsel, 2004). However, only three sequences of this species were detected in this study, suggesting that this species was exiguous in the research area.…”
Section: Effects Of Fertilization On Amf Abundance and Community Strumentioning
confidence: 67%
See 1 more Smart Citation
“…The fact that all AMF taxa used in this study belonged to the same genus (Glomus) may, thus, explain why there was no effect of AMF diversity on plant productivity. European arable soils subjected to regular ploughing are regularly dominated by members of the Glomeraceae (Daniell et al 2001;Hijri et al 2006;Alguacil et al 2008;Verbruggen et al unpublished results). Hence, the use of only Glomus species in our experiment is comparable to a situation regularly found in the field.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, plants in the sterile soil treatment may have been of increased quality to aphids compared with those on non-sterile soil due to compromised plant defences or more rapid onset of senescence, which can increase the flux of nutrients into the phloem to the benefit of phloem-feeding herbivores [24]. By contrast, no significant difference was observed in total plant biomass between the cultivated and uncultivated soil treatments, despite the fact that the disruptive effects of tillage [10,11] were likely to have reduced microbial diversity in the cultivated soil [25]. Although previous work [26] has demonstrated variability in total plant responses to soil community diversity, cultivated plants may be less likely to respond to variation in soil microbial communities [27].…”
Section: Discussionmentioning
confidence: 99%